Simulation of Single Phase SPWM Full Bridge Inverter Using Different Control Techniques - Ahkam Kamil Naji (Journal of Madenat Alelem University College, 2019)
this paper presents two control algorithms using two different feedback controls for a SPWM single phase inverter to obtain pure 50 Hz output sinusoidal voltage, the plan is to employ each controller with its particular features for controlling the SPWM single phase inverter. The first technique is done with a traditional Proportional-Integral (PI) controller and the second technique is done with the Fuzzy Logic Control (FLC), the efficiency of the offered scheme is tested under various operating conditions. The offered scheme has shown good performance regarding output voltage distortion, very good voltage chasing even under load inconstancy. This system is used with grid-solar energy systems; induction heating and uninterruptible power supplies (UPS).